2016
DOI: 10.3928/01484834-20160816-04
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Students Squirm: Nursing Students' Experiences of Bullying Behaviors During Clinical Rotations

Abstract: Background Bullying remains a troubling problem in the nursing profession. Nursing students may encounter bullying behavior in clinical settings. However nursing students may not be adequately prepared to recognize and handle bullying behavior when it occurs. The purpose of this study was to gain greater understanding of nursing students’ experiences of bullying behaviors in the clinical setting. Method Using a descriptive qualitative approach, eight focus groups were held with 56 undergraduate baccalaureate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 19 publications
(34 reference statements)
4
58
0
4
Order By: Relevance
“…It is an opportunity for them to practice and hone their clinical skills while at the same time developing habits and behaviours that will help to shape them into a competent health care professional in the context of real-world time pressures and resource restraints. The comments made by respondents in this study have shown that nursing students are experiencing an additional burden that permeates these important opportunities in their professional development, findings that echo those of earlier work (Bowllan, 2015;Smith, Gillespie, Brown, & Grubb, 2016).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…It is an opportunity for them to practice and hone their clinical skills while at the same time developing habits and behaviours that will help to shape them into a competent health care professional in the context of real-world time pressures and resource restraints. The comments made by respondents in this study have shown that nursing students are experiencing an additional burden that permeates these important opportunities in their professional development, findings that echo those of earlier work (Bowllan, 2015;Smith, Gillespie, Brown, & Grubb, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…The findings show that the participants experienced being belittled, humiliated, criticised, excluded and subjected to various forms and degrees of verbal, physical and, sexual and racial abuse. In a recent study, Smith et al (2016) cited similar examples of bullying behaviours, although these were primarily non-physical. That study also described students being exposed to non-verbal behaviours such as eye-rolling that reflect the passive-aggressiveness experienced by participants in the current study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Reported reasons newly licensed nurses are targeted for bullying include bullying being a rite of passage, a norm against new employees, and a result of environmental/organizational factors such as high job demand. [15] …”
Section: Introductionmentioning
confidence: 99%